Pelatihan Pembuatan Media Pembelajaran Bagi Guru dengan Aplikasi Pembelajaran Berbasis Literasi Digital - Muntahanah; Harry Witriyono; Rozali toyib; Sastya Wibowo; Dedy Prabowo; Yulia Darnita; Yulia Darmi (Ikatan Ahli Informatika Indonesia, 2022)
Learning activities are basically an effort to direct students into the learning process so that they can obtain learning objectives in accordance with what is expected. teaching and learning activities run properly, these activities are a process of teachers and students interacting with each other which will have a reciprocal relationship. influencing and influenced, the success of learning can be seen from many factors, namely the teacher and the students themselves. The problem is changing the habits of teachers who used to use the old method focusing on books and modules. They will have difficulty dealing with online teaching and learning activities. training is needed, it is possible to make interactive, digital-based learning media, which makes it possible to use the Covid-19 pandemic condition, which demands online or semi-annual teaching. offline. After attending the training, participants are expected to be able to take advantage of learning technology and take advantage of multimedia developments to create good learning media with Kinemaster, make attractive presentations using Canva with interesting features, VSDC Video Editor to create interactive learning need on going activities because most of the participants still need training to help the learning process lead to digital system, online-based and independent learning